A framework and implementation of the Customer-to-Manufacturer (C2M) paradigm - Yanglang Yuan; Jingke Wang; Guyue Zhou; Yiming Rong; Yongsheng Ma (Advanced Manufacturing)
With the advancement of pervasive commerce on the Internet, the way to purchase consumer products has been changing to personalized products with preferred individual customization. A new manufacturing paradigm named “Customer-to-Manufacturer (C2M)” has been prevalent in the E-commerce sector and the context of Industry 5.0. It establishes a direct connection between consumers and manufacturers via E-commerce platforms, allowing individual clients to participate in the model design process alongside engineers to fulfill their specific requirements. Moreover, it aims to provide manufacturers with systematic approaches for producing customized products more efficiently, resulting in shorter delivery times, lower inventory costs, and higher customer satisfaction and loyalty. In this paper, the authors briefly review the evolution of the manufacturing paradigm, suggest a structurally well-defined C2M concept, and propose a framework for C2M that utilizes contemporary digital technologies in the context of Industry 5.0 to streamline the manufacturing-to-delivery process through intelligent, human-centric, resilient, and environment-friendly design and manufacturing solutions. Additionally, a case study for the implementation of C2M has been explored. The findings of this study suggest that the C2M paradigm is an effective way to meet the growing demand for customization and personalization in E-commerce. It not only improves customer satisfaction and loyalty but also has the potential to improve supply chain efficiency and reduce costs for both sides. E-commerce retailers or manufacturing enterprises may consider adopting a C2M paradigm for online customization to stay competitive in a rapidly evolving market.